What are ʾElilim? - Hamilton, Mark W. (The journal of Hebrew scriptures, 2019)
The Hebrew word ᵓĕlīlîm is usually explained as the plural of the Hebrew adjective ᵓĕlīl (“useless, vain”), hence a dysphemism describing idols. However, the ancient versions did not understand the word this way. The word more plausibly is a loanword from the Akkadian illilu, itself a borrowing from Sumerian. The earliest attestations of ᵓĕlīlîm in Hebrew appear in Isaiah often as part of code-switching to signal the foreignness of the word itself.